Multidimensional pooled shRNA screens in human THP-1 cells identify candidate modulators of macrophage polarization. - Ewa Surdziel; Ieuan Clay; Florian Nigsch; Anke Thiemeyer; Cyril Allard; Gregory Hoffman; John S Reece-Hoyes; Tanushree Phadke; Romain Gambert; Caroline Gubser Keller; Marie-Gabrielle Ludwig; Birgit Baumgarten; et al. (PLoS ONE, 2017)
Macrophages are key cell types of the innate immune system regulating host defense, inflammation, tissue homeostasis and cancer. Within this functional spectrum diverse and often opposing phenotypes are displayed which are dictated by environmental clues and depend on highly plastic transcriptional programs. Among these the 'classical' (M1) and 'alternative' (M2) macrophage polarization phenotypes are the best characterized. Understanding macrophage polarization in humans may reveal novel therapeutic intervention possibilities for chronic inflammation, wound healing and cancer. Systematic loss of function screening in human primary macrophages is limited due to lack of robust gene delivery methods and limited sample availability. To overcome these hurdles we developed cell-autonomous assays using the THP-1 cell line allowing genetic screens for human macrophage phenotypes. We screened 648 chromatin and signaling regulators with a pooled shRNA library for M1 and M2 polarization modulators. Validation experiments confirmed the primary screening results and identified OGT (O-linked N-acetylglucosamine (GlcNAc) transferase) as a novel mediator of M2 polarization in human macrophages. Our approach offers a possible avenue to utilize comprehensive genetic tools to identify novel candidate genes regulating macrophage polarization in humans.